MAKNA SIMBOLIK RITUAL PENGOBATAN TRADISIONAL TOGAK BELIAN DI DESA KOTO RAJO KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Rani Ardina; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Ritual togak belian is one of traditional culture of Riau people. There are symbolic in ritual togak belian with special meaning that is represented by sesajen, musical instrument in ritual togak belian, and mantra in ritual togak belian. The purpose of this research was determining the meaning of dymbolic situation, the product of social interaction, and the interpretative of ritual togak belian as traditional treatment in Koto Rajo Village. This research used qualitative methode by symbolic interaction approach. Informant of this research is togak belian’s shaman, public figure who were selected by using purposive techniquw, and togak belian’s patient were selected by using accidental technique. Data collage technique used observation, interview, and documentation. The result of research showed that symbolic of ritual togak belian as traditional treatment in Koto Rajo society include physical objects such as sesajen and musical instrument in togak belian (gendang, genta) with special meaning in every part while the social objects from ritual togak belian include the movement of togak belian’s shaman (fast movement and slow movement),mantra on ritual togak belian and object social have meaning to call supernatural beings and to say thanks for them. The meaning of social product’s interaction includes the meaning of ritual togak belian’s shaman side where the shaman interpret ritual togak belian has tradition value and to help people sick who need ritual togak belian as traditional treatment, from public figure of Koto Rajo people’s side ritual togak belian has indigenous traditions,historis value, sacredness, togetherness and concern value and from ritual togak belian’s patient side ritual togak belian has trust value, social value, economy value and system traditional treatment also alternative treatment. Interpretation’s meaningof ritual togak belian include closed action and the opened action. The closed action include internal and external motivation of togak belian’s shaman and both of scientific heritage hereditary and public demand. The opened action of ritual togak belian’s shaman include the expression of shaman and the attitude of shaman who were always compact and have a good teamwork the both of shaman.Keyword: Symbolic Meaning, Ritual Togak Belian, Symbolic situation, The Product of Social Interaction, Interpretation